APLIKASI DIAGNOSA GEJALA DEMAM PADA BALITA MENGGUNAKAN METODE CERTAINTY FACTOR (CF) DAN JARINGAN SYARAF TIRUAN (JST) - Maharani, Septya; Adi, Kusworo; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Symptoms of fever of toddlers have a devastating effect if too late to get treatment is not appropriate, to make it easier for parents to detect the type of disease, it is necessary to build an expert system application detection of disease symptoms of fever in children for early detection of disease. Knowledge base is implemented as a basis for expert system applications by using a combination of certainty factors (certainty factor) and ANN (artificial neural networks). Methods This study is a combination of CF as CF is the rule and the results will form a pattern which is a merger of the ANN clinical parameter that indicates the amount of trust as the knowledge base of disease diagnosis of fever in children 10 to 40 symptoms, the system uses a total of 40 symptoms as a medic training data with records of 20 patients. From the results of such testing, the application has been concluded at 86.67% accuracy rate. Â  Keywords: fever, expert systems, Certainty Factor, Neural Networks